The iBRA-2 (immediate breast reconstruction and adjuvant therapy audit) study: protocol for a prospective national multicentre cohort study to evaluate the impact of immediate breast reconstruction on the delivery of adjuvant therapy. Issue 10 (7th October 2016) - Dave, Rajiv; O'Connell, Rachel; Rattay, Tim; Tolkien, Zoe; Barnes, Nicola; Skillman, Joanna; Williamson, Paula; Conroy, Elizabeth; Gardiner, Matthew; Harnett, Adrian; O'Brien, Ciara; Blazeby, Jane; et al.
Abstract : Introduction: Immediate breast reconstruction (IBR) is routinely offered to improve quality of life for women with breast cancer requiring a mastectomy, but there are concerns that more complex surgery may delay the delivery of adjuvant oncological treatments and compromise long-term oncological outcomes. High-quality evidence, however, is lacking. iBRA-2 is a national prospective multicentre cohort study that aims to investigate the effect of IBR on the delivery of adjuvant therapy. Methods and analysis: Breast and plastic surgery centres in the UK performing mastectomy with or without (±) IBR will be invited to participate in the study through the trainee research collaborative network. All women undergoing mastectomy ± IBR for breast cancer between 1 July and 31 December 2016 will be included. Patient demographics, operative, oncological and complication data will be collected. Time from last definitive cancer surgery to first adjuvant treatment for patients undergoing mastectomy ± IBR will be compared to determine the impact that IBR has on the time of delivery of adjuvant therapy. Prospective data on 3000 patients from ∼50 centres are anticipated. Ethics and dissemination: Research ethics approval is not required for this study. This has been confirmed using the online Health Research Authority decision tool. This novel study will explore whether IBR impacts the time to delivery of adjuvant therapy. The study will provide valuable information to help patients and surgeons make more informed decisions about their surgical options. Dissemination of the study protocol will be via the Mammary Fold Academic and Research Collaborative (MFAC) and the Reconstructive Surgery Trials Network (RSTN), the Association of Breast Surgery (ABS) and the British Association of Plastic, Reconstructive and Aesthetic Surgeons (BAPRAS). Participating units will have access to their own data and collective results will be presented at relevant surgical conferences and published in appropriate peer-reviewed journals.